Investigating Relationships Between Work and Sleep and Their Mutual Consequences for Well-Being: An Actigraphy-Based Ambulatory Assessment Approach - Janurek, Janina Uschi; Justus Liebig University Giessen (My University, 2022)
In five studies, this dissertation pursues three main objectives including (1) the investigation of work-related antecedents of (poor) sleep, (2) the investigation of mutual consequences of time spent working and time spent sleeping for well-being, and (3) a methodological examination of actigraphy as a more objective measurement of sleep. Specifically, in Studies 1 (a two-wave online study), 2 and 3 (7-day ambulatory assessment studies with a morning and an evening survey each day, including actigraphy as an objective measurement of sleep in addition to self-reports), I investigated the relationships between job demands, work-related rumination and sleep. Consistently across these three studies, results showed that work-related rumination mediates the relationship between job demands and subjective sleep quality, but not sleep duration. In Study 4 (a 7-day ambulatory assessment study with morning surveys each day, including actigraphy), I investigated the effects of time spent working and time spent sleeping on emotional exhaustion as an indicator of well-being, using a compositional data analysis approach. Results showed that time spent working is positively related to emotional exhaustion, but there was no significant association between time spent sleeping and emotional exhaustion. Finally, in Study 5 (14-day field experiment including actigraphy), I investigated reactivity to the actigraphic measurement of sleep by manipulating the communicated measurement intention (sleep vs. physical activity). Results showed no evidence for reactivity to measurement in the context of the actigraphic measurement of sleep. Therefore, results obtained from actigraphy in this dissertation (cf., Studies 2, 3, & 4) can be deemed reliable with regards to measurement reactivity, and the same applies to actigraphy as a more objective measurement of sleep in general. In sum, the results of Studies 1-4 point out the importance of a healthy work-environment (i.e., job demands not too high, working hours not too long) for an individual’s health and well-being (i.e., sleep quality & emotional exhaustion) and emphasize the potentially detrimental effects of unsuccessful psychological detachment from work in the form of work-related rumination during non-work time.
Keywords: ddc:150